2022
DOI: 10.3390/vaccines11010007
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Risk Perception and Adherence to Preventive Measures among Medical Students after Receiving COVID-19 Vaccination: A Multicenter Cross-Sectional Study in Egypt

Abstract: This study aimed to assess the perception of COVID-19 risk and the adherence to protective measures among medical students after vaccination. We conducted a cross-sectional survey on a convenience sample of students from all the 18 governmental medical schools in Egypt. A total of 2273 students participated in the online self-administered questionnaire. Around 8 in 10 (83.2%) students were fully vaccinated, of which 17.9% received the booster dose. Only 36.9% believed that COVID-19 is serious on the individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…[50][51][52][53][54][55] With regard to COVID-19, several studies have shown that both women working in the medical field and female students working in medical and non-medical fields rated risk more highly. 56,57 Differences in risk perceptions cannot be explained by differences in knowledge. As Licata et al observed, gender does not affect students' knowledge of COVID-19, but it does affect risk perceptions and health behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52][53][54][55] With regard to COVID-19, several studies have shown that both women working in the medical field and female students working in medical and non-medical fields rated risk more highly. 56,57 Differences in risk perceptions cannot be explained by differences in knowledge. As Licata et al observed, gender does not affect students' knowledge of COVID-19, but it does affect risk perceptions and health behaviors.…”
Section: Discussionmentioning
confidence: 99%